Aurora Borealis: Scientific Mechanisms, Geomagnetic Influences, and Cultural Significance - Hidayatullah Mashhood; Naqib Ahmad Nori (Social Science Academic, 2025)
The Aurora Borealis, or Northern Lights, is a luminous atmospheric phenomenon resulting from complex interactions between charged particles in the solar wind and Earth's magnetosphere. This paper investigates the scientific mechanisms that produce auroral displays, including geomagnetic processes, atmospheric interactions, and variations in light color and intensity. Additionally, it explores the historical, cultural, and mythological interpretations of auroras across diverse societies, from Inuit legends and Norse mythology to Asian and Indigenous American beliefs. By integrating astrophysical analysis with anthropological perspectives, this study emphasizes the multifaceted significance of auroras, highlighting their role in advancing scientific understanding, inspiring artistic expression, and shaping cultural narratives. The findings underscore the interplay between natural phenomena, human perception, and technological observation in interpreting the Northern Lights.